Modified muscle sparing posterolateral thoracotomy. - Ashour, M (1990)
A modified posterolateral thoracotomy is described that combines the advantages of complete muscle sparing through a thoracolumbar fascial slide with excellent exposure. The technique is easy to perform. The procedure was associated with relatively little postoperative pain, coughing was effective, and early ambulation was achieved. Experience with this approach in the first 49 patients suggests that it offers an attractive alternative to the standard muscle cutting posterolateral thoracotomy approach for elective procedures.